Biomarker-driven drug repurposing on biologically similar cancers with DNA-repair deficiencies - Munj, Seeya Awadhut; Taz, Tasnimul Alam; Arslanturk, Suzan; Heath, Elisabeth I. (Frontiers in Genetics, 2022)
Similar molecular and genetic aberrations among diseases can lead to the discovery of jointly important treatment options across biologically similar diseases. Oncologists have closely looked at several hormone dependent cancers and identified remarkable pathological and molecular similarities in their DNA repair pathway abnormalities. In this paper, through a biomarker-driven drug repurposing model, we have identified several potential drug candidates for breast and prostate cancer patients with DNA-repair deficiencies based on common specific biomarkers and irrespective of the organ the tumors have originated from. Normalized discounted cumulative gain (NDCG) and sensitivity analysis have been used to assess the performance of the drug repurposing model. Our results have shown that Mitoxantrone and Genistein are among drugs with high therapeutic effects by significantly reverting the gene expression changes caused by the disease (FDR adjusted p-values for prostate cancer =1.225e-4 and 8.195e-8, respectively) for patients with deficiencies in their homologous recombination (HR) pathways. The proposed multi-cancer treatment framework, suitable for patients whose cancers have common specific biomarkers, has the potential to identify promising drug candidates by enriching the study population through the integration of multiple cancers and targeting patients who respond poorly to organ-specific treatments.